5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6
The given expression can be simplified to: 3X squared +27
The answer is -8.
x= 9
2x+9 = 49-3x 2x+3x = 49-9 5x = 40 x = 8
(5x 2 - 8x + 1) + (2x 2 - 4x - 11)
5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6
5x + 4 - 3x + 5 + 2x - 9 = 4x
The given expression can be simplified to: 3X squared +27
6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1
if you meant 5x+9=3*15 then, 5x = 36, x = 7.2 if you meant 5x+9=3x+15 then, 2x = 6, x = 3
The answer is -8.
3x + 9 = 5x - 43x +13 = 5x13 = 2x13/2 = xso x = 6.5
x= 9
The problem '3x+9=81-5' can be solved as follows - 3x+9=81-5x Original Problem 3x=72-5x Subtract 9 from both sides of the equation 8x=72 Add '5x' to both sides of the equation x=9 Divide both sides by 8
2x+9 = 49-3x 2x+3x = 49-9 5x = 40 x = 8
5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3